South African Mathematics Curriculum Framework’s dimensions for Grade 9 mathematics content standards and summative assessment tasks - Agnes Dulu Qhibi; Thelma De Jager; Cornelius Johannes White (Perspectives in Education)
The South African Department of Basic Education (DBE) has established the Mathematics Curriculum Framework (SAMCF) to enhance learning, teaching, and assessment in mathematics, and help learners with conceptual understanding and consequently improve mathematics performance. Thus, teachers are expected to synchronise the SAMCF’s dimensions in teaching and assessment. This study attempted to establish the extent to which the Grade 9 mathematics content standards and the Grade 9 mathematics summative assessment tasks align with the SAMCF’s dimensions before fully implementing the framework. The aim was to guide curriculum policymakers on what needs to be reviewed by applying the mathematical proficiency strands as a theoretical framework. A quantitative document analysis was used to explain the level of the mathematical proficiency strands. Four summative assessment tasks from November 2022 were purposively sampled from the four districts of Mpumalanga province to analyse. The findings revealed substantial misalignment between the Grade 9 mathematics content standards and the summative assessment tasks. While the Grade 9 mathematics content standards were found to promote conceptual understanding, the summative assessment tasks promoted procedural fluency. The study recommends that the SAMCF’s dimensions be explicitly quantified in percentages to guide teachers and examiners on how much they should be covered in the summative assessment tasks. Also, it is suggested that the productive disposition dimension be added in the SAMCF’s dimensions to inspire learners’ positive attitudes towards learning mathematics. Furthermore, it is recommended that future studies should investigate the alignment between SAMCF’s dimensions on summative assessment tasks and content standards for other grades to ensure that the envisaged SAMCF’s goals are realised.